PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA BANK BTN (PERSERO) CABANG BEKASI - Paramita, Widya; Prayuda, Wendi Hadi; Handaru, Agung Wahyu (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2013)
The purpose of the research are: 1) To know description for working environment, organization culture, and job satisfaction at Bank BTN (Persero) cabang Bekasi. 2) to test the influence of working organization towards job satisfaction at Bank BTN (Persero) cabang Bekasi. 3) to test tthe influence of organization culture towards job satisfaction at Bank BTN (Persero) cabang Bekasi. 4) to test the influence of working environment and organization culture towards job satisfaction at Bank BTN (Persero) cabang Bekasi. The analysis implemented in this research are simple regression and multiple regression analysis. The method of this research is simple random sampling, that taken 55 Operational Division employee at Transaction Process Division, Loan Administration Division, and General Administration Division, while data collecting by using questionnaire and cultivated using SPSS 19.0. The result of t test for working environment is 2.123, and the signification is 0.038. This shows that there is an effect between working environment toward job satisfaction. The result of t test for organization culture is -2.160 ,and the signification is 0.035 This shows that there is an effect between organization culture toward job satisfaction. The result of F test is 5.798, and the signification is 0.005. This shows that there is an effect between working environment and organization culture toward job satisfaction. The result of R2 is 0.182 or 18,2%. It means Job Satisfaction is affected by working environment and organization culture as much as 18,2%. Keywords: working environment, organization culture, job satisfaction